Effect of Exercise on Disorders of Carbohydrate and Lipid Metabolism in Adults With Traumatic Spinal Cord Injury: Systematic Review of the Evidence - Carlson, Kathleen F.; Wilt, Timothy J.; Taylor, Brent C.; Goldish, Gary D.; Niewoehner, Catherine B.; Shamliyan, Tatyana A.; Kane, Robert L. (The journal of spinal cord medicine, 2009)
Background/Objective: Carbohydrate and lipid metabolism disorders may affect adults with spinal cord injuries (SCIs) differently than able-bodied individuals because of reduced physical activity in the SCI population. The objective of this study was to conduct a systematic review to determine the effectiveness of exercise to improve carbohydrate and lipid metabolism disorders in adults with chronic SCI. Methods: Studies were identified in MEDLINE (1996-2008), Cochrane Library, bibliographies of identified articles, and expert recommendations. English language articles were included if they evaluated adults with chronic SCI; evaluated exercise; and reported carbohydrate-, lipid-, and/or cardiovascular disease-related outcomes. Results: Twenty-two studies met inclusion criteria, including 15 intervention case-series and 7 crosssectional surveys using self-reported physical activity measures. Intervention protocols involved active (n = 7) or electrically stimulated (n = 7) exercise or an educational program (n = 1) from 8 to 52 weeks in duration. Frequency of exercise was typically 2 to 3 sessions/week, lasting 30 to 60 minutes/session. Totals of 150 and 369 subjects participated in studies with carbohydrate (n = 12) or lipid and cardiovascular (n = 16) outcomes, respectively; 78% were men. Level of SCI ranged from C4 to L5 and included both incomplete and complete lesions. Outcomes measures included fasting and postload blood glucose and insulin concentrations and serum cholesterol levels. Small sample sizes and variations in study design, intervention, SCI characteristics, and reported outcomes precluded quantitative pooling of results or reliable assessment of metabolic efficacy. No intervention studies assessed cardiovascular outcomes. Conclusions: Evidence is insufficient to determine whether exercise improves carbohydrate and lipid metabolism disorders among adults with SCI. Expert consensus, based on the preliminary evidence, is needed to inform future studies.